Curriculum implementation: strategies for mounting listening skills among junior secondary school students - Adebayo A. Bello (Journal of Pedagogical Research, 2018)
Education requires rethinking as the country faces the demands of educational and socio-economic transformation of different kinds such to provide learners' opportunities to acquire knowledge; to have skills for literacy, numeracy, creativity and ability to have free communication and listening skills. The purpose of this research was to examine the strategies that can be used to develop listening skills needed for junior secondary school students. The methodology used for the study was survey research design. The sample consisted of staff and junior students with the total of 271. The majority of those who filled the questionnaires reported that many students were not found to be willing to be in the class. It was only a few who responded to their teacher. Many students remain dull because teachers are not using the appropriate method of teaching thereby making the class bored for them. Majority of the respondents disagree that teachers don't give instruction in the class. It was therefore, recommended that teachers/staff should instruct the students to have more extensive listening in their spare time, provide media and other resource that can aid teaching and enhance students' comprehension in class. These can give them a quick flash back even while at home, hence supporting improved curriculum implementation and ultimately improved listening skill, for academic success comes from listening and from what is or has been thought either inside or outside of the classroom.